2021
DOI: 10.48550/arxiv.2111.12058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insignificance of the anomalous magnetic moment of the quarks in presence of chiral imbalance

Nilanjan Chaudhuri,
Arghya Mukherjee,
Snigdha Ghosh
et al.

Abstract: We incorporate the anomalous magnetic moment (AMM) of quarks in the framework of PNJL model to study hot and dense magnetised matter with chiral imbalance. For this purpose, the eigen energy solution of the Dirac equation is obtained in presence of constant background magnetic field and chiral chemical potential (CCP) along with the minimal anomalous magnetic moment interaction of the fermion. Although there is a marginal enhancement in the IMC behaviour of the quark condensate due to the combined effects of A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Here > 0 represents the energy eigenvalues of the quarks considering the finite values of AMM and is given by [65,68] 2…”
Section: A Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Here > 0 represents the energy eigenvalues of the quarks considering the finite values of AMM and is given by [65,68] 2…”
Section: A Formalismmentioning
confidence: 99%
“…In Refs. [51,[65][66][67][68][69][70][71][72][73][74], it is observed that the consideration of nonzero values of the anomalous magnetic moment (AMM) of the quarks results in a decrease in chiral transition temperature implying IMC.…”
Section: Introductionmentioning
confidence: 99%
“…The 'strong' interaction of quarks has been modeled using the 2-flavour Nambu-Jona-Lasionio (NJL) model [59,60] in the mean field approximation. This model has been extensively used to examine some of the nonperturbative properties of the QCD at arbitrary values of temperature and baryon chemical potential (BCP) (see [61][62][63] for reviews), as well as in presence of a CCP [64][65][66][67][68][69][70]. The constituent quark mass at different external parameters, such as temperature, BCP and CCP, has been obtained by solving the corresponding gap equation.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, we have used the Nambu-Jona-Lasinio (NJL) model [61,62] which is built by respecting the global symmetries of QCD, most importantly the chiral symmetry [63][64][65]. This model has been very useful to probe the vacuum structure of QCD at arbitrary values of temperature, baryon chemical potential (BCP) and CCP [66][67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%